A Cooperative Environment for Local Government: An Internet – Intranet Approach - Christos Bouras; Vasilis Triantafillou; P Destounis; J Garofalakis; J Tzimas; P Zarafidis (Journal of Telematics and Informatics, Elsevier Science, Vol. 16, Issue 1-2, 1999)
In this paper we present a Web-based, database oriented CSCW system to support information dispersal between di€erent Local Government authorities (Region, Prefecture and Municipalities) and the citizens. The system is implemented around the `shared workspace' notion, a group of directories and ®les controlled by the users of the workspace. Intranet and Extranet technologies are exploited to enable asynchronous and synchronous co-operation, manipulation of information from heterogeneous sources, security and easy administration, providing in parallel advanced communication facilities. We propose an innovative approach for the development of shared workspaces over WWW, based on state-of-the-art software platforms, integrating WWW and database technologies. The whole system was developed under a project funded by the Greek General Secretariat of Research and Technology and aims in the ecient distribution and management of information between and within di€erent types of local authorities (Municipalities, Prefectures).